2007
DOI: 10.1002/ijc.22858
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of E‐cadherin and β‐catenin by Ca2+ in colon carcinoma is dependent on calcium‐sensing receptor expression and function

Abstract: An siRNA directed against the extracellular calcium‐sensing receptor (CaSR) was used to down‐regulate this protein in CBS colon carcinoma cells. In additional studies, we utilized a variant of the parental CBS line that demonstrates CaSR expression but does not upregulate this protein in response to extracellular Ca2+. In neither the siRNA‐transfected cells nor the Ca2+‐nonresponsive variant cells did inclusion of Ca2+ in the culture medium inhibit proliferation or induce morphological alterations. Extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 33 publications
7
89
1
Order By: Relevance
“…11,14 In a small series of colorectal cancer tissues (n ¼ 6), a relationship between CASR expression and b-catenin staining pattern was reported. 14 In this study, nuclear/cytoplasmic b-catenin expression was more frequently observed in cases with reduced CASR expression than in cases with normal CASR expression. As various genetic and epigenetic alterations are involved in b-catenin/T-cell factor activation, the relationship between b-catenin expression and CASR expression seems not to be simple.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,14 In a small series of colorectal cancer tissues (n ¼ 6), a relationship between CASR expression and b-catenin staining pattern was reported. 14 In this study, nuclear/cytoplasmic b-catenin expression was more frequently observed in cases with reduced CASR expression than in cases with normal CASR expression. As various genetic and epigenetic alterations are involved in b-catenin/T-cell factor activation, the relationship between b-catenin expression and CASR expression seems not to be simple.…”
Section: Discussionmentioning
confidence: 99%
“…CASR reportedly controls proliferation and differentiation in the human colonic epithelium and colon carcinoma cells. [10][11][12][13][14][15][16][17][18] Increased thymidylate synthase expression is one the most important mechanisms underlying the resistance to 5-fluorouracil (FU) in colorectal cancer. 19,20 Interestingly, activation of CASR reportedly downregulates the expression of thymidylate synthase and survivin, and upregulates cellular sensitivity to 5-FU in human colorectal cancer cell lines.…”
mentioning
confidence: 99%
“…Since CaSR not only suppressed protein expression of survivin and TS, but also inhibited gene promoter transcription of these proteins, we suggested that the suppression of the genes by CaSR mainly occurred at the level of transcriptional promotion and initiation. Activation of CaSR also stimulates the expression of E-cadherin (8,9,36). E-cadherin is a major classical trans-membrane protein in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Human colon carcinoma cell line CBS, Moser, Fet, and SW480 cells were maintained in SMEM medium (Sigma, St. Louis, MO) as described previously (7)(8)(9). To assess the effect of the compounds indicated on the cytotoxic response to anticancer drugs, the medium of actively growing cells was replenished with medium containing the compounds at the doses indicated in the figures and FOLFIRI (5-FU 60 μM, leucovorin 28 μM, SN-38 40 μM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation